Analisis Sistem Manajemen Keselamatan dan Kesehatan Kerja Menggunakan Metode Hazard Identification Risk Assessment (Hira) - St. Nova Meirizha; Elsa, Elsa Heliana (SURYA TEKNIKA, 2023)
PT Lutvindo Wijaya Perkasa is a company engaged in the field of general contractor, marketing, service and suppliers. In the asphalt and concrete production process at PT Lutvindo Wijaya Perkasa there are still employees who do not pay attention to work procedures, do not use complete PPE, such as not using project helmets, safety shoes, masks, goggles and ear plugs. So there are still work accidents. Based on the results of work accident interviews that often occur at PT Lutvindo Wijaya Perkasa, namely falls from heights, collisions, hearing loss, slipping, and electric shock. Hazard Identification and Risk Assessment (HIRA) is one of the methods used to control the risk of work accidents and carry out a risk assessment, which aims to prevent work accidents that can occur. This research was conducted to reduce accidents that can occur at PT Lutvindo Wijaya Perkasa. The results of the study using the HIRA method found 8 findings of potential hazards in the production area of ​​PT Lutvindo Wijaya Perkasa with moderate to extreme levels of risk.